Efficiency of combined co-composting, vermicomposting, and drying in the treatment of cadmium, mercury, helminths, and coliforms in sludge from wastewater facilities for potential agricultural applications - Guzman, Maria Aileen Leah G.; Dumo, Joan Ruby E.; Unson, Jewel Racquel S.; Espiritu, Emilyn Q.; Estiva, Jude Anthony N.; Del Castillo, Marylle F.; Udtojan, May Ann A.; Espinas, Jay Roy E. (2020)
Sludge generated from wastewater treatment facilities has been applied in agriculture as soil conditioners. However, the incomplete and/or inappropriate treatment of wastewater may result in sludge that may still contain heavy metals, helminth ova, and coliforms posing a risk to both humans and the environment. This study assessed various pretreatment techniques such as co-composting, vermicomposting, and a combination of these on sludge samples to remove heavy metals (cadmium and mercury), helminth ova, and coliforms. Physico-chemical and biological analyses were used to compare untreated (i.e. raw) and treated sludge samples. The results showed that for the raw sludge, mercury (4.02 +/? 0.17 mg/kg) and cadmium (6.30 +/? 0.48 mg/kg) exceeded the limits specified under the Philippine National Standard (PNS) for Organic Soil Amendments of 2 mg/kg and 5 mg/kg, respectively. Laboratory examinations also revealed the presence of helminth ova (5 ova/g) and coliforms (10 CFU/g) in the samples. Sludge samples subjected to a combination of co-composting and vermicomposting resulted in the elimination of mercury and a significant reduction in cadmium concentration from 6.30 mg/kg to 1.12 mg/kg. No helminth ova were observed in the samples after further drying. However, both treated and untreated sludge samples had low nutrient content. The study highlights the need for raising public awareness and educating farmers on the potential risks associated with the use of raw sludge for agriculture. (Author's abstract)